Análisis metrológico de la instrumentación asociada en el motor de combustión del laboratorio de experimentos de la UAN-Sede Puerto Colombia (2021)
The justification for the work is based on the need to know the metrological reliability of the temperature and mass measurement system of the internal combustion engine fuel at the UAN-Puerto Colombia Headquarters. To this end, the application of the ordinary least squares (OLS) method as a strategy to reduce the uncertainty associated with the measurement equipment used in industry to control various quantities (for example: mass, temperature, volume, pressure). Initially, the theoretical foundation of the exposed method will be addressed (that is, ordinary least squares), widely highlighting the mathematical formulation, based on the classic concepts of linear algebra. In line with the proposed work, an analysis will be carried out based on obtaining: (i) the matrix of coefficients for polynomials of degree 1, 2, 3 and 4 that fit the experimental data; (ii) draw the calibration curves for each of the polynomials obtained and (iii) estimate the uncertainty of the fit (that is, the mean squared deviation) to specify the polynomial that best models the experimental data for a confidence level of 95.45 % (k = 2). The consolidated results confirmed that the thermometers associated with the internal combustion engine temperature measurement system have errors that do not exceed 5% of the measurement value. Likewise, the fuel consumption measurement system does not exceed 6% of the measured value. In both cases, the measurement uncertainty was considered a fundamental parameter for the metrological evaluation, obtaining values within the tolerance range for the type of test bench used. Thus, the results confirmed that the temperature and fuel consumption measurement system are satisfactory to carry out experimental tests on the engine.